A multitheoretical approach for solving trust problems in B2C e-commerce. (20th June 2008) - Pittayachawan, Siddhi; Singh, Mohini; Corbitt, Brian
Trust has been identified as a major barrier in online shopping, especially in the B2C e-commerce model. It has been studied for several years, but there is no indicator that a satisfactory solution for trust in online shopping has been achieved. A trust model is proposed in this paper in order to address this issue. It is uniquely based on five current issues (cybercrime, security, control, web interface, and a trusted third party) that impact trust, guided by four supportive theories: Semiotics, Trust in Signs, Simmelian Model of Trust and Trustworthiness. The research was accomplished with an online survey to collect data from online shoppers around the world. Structural Equation Modelling (SEM) was used to validate the trust model revealing that privacy and security of information are most important factors affecting trust in B2C e-commerce followed by web interface and control.